Experimental and numerical insights into heterogeneous liquid-solid behaviour in drinking water softening reactors. (August 2021) - Nijssen, T.M.J.; Kramer, O.J.I.; de Moel, P.J.; Rahman, J.; Kroon, J.P.; Berhanu, P.; Boek, E.S.; Buist, K.A.; van der Hoek, J.P.; Padding, J.T.; Kuipers, J.A.M.
Graphical abstract: Highlights: Liquid-solid fluidisation experiments show open spaces at low velocities. Heterogeneous particle–fluid patterns are detected at higher fluid velocities. CFD-DEM simulations show good agreement with experimental observations. Numerical simulations confirm the formation of local voids and instabilities. Voidage distributions and solid flux profiles obtained from our computer simulations. Abstract: Liquid-solid fluidisation is frequently encountered in drinking water treatment processes, for instance in seeded crystallisation softening processes. For modest superficial fluid velocities, liquid–solid fluidisation systems are generally considered to be homogeneous, as reported in literature. However, during fluidisation experiments with calcite grains, open spaces of water can be observed between the fluidised particles, even at relatively low fluid velocities. Moreover, significant heterogeneous particle–fluid patterns are detected at higher fluid velocities. Such heterogeneous behaviour can beneficially or adversely affect the chemical crystallisation efficiency. To obtain information about voids in bulk regions, complementary Computational Fluid Dynamics - Discrete Element Method (CFD-DEM) simulations were performed and compared with the experimental results for validation. Simulations were performed using different water inlet velocities and fractionised calcite granules obtained from full-scale reactors. Here, the results are analysed using the bed height, voidage and pressure drop of the system. Furthermore, images of the experiments and simulations are visually compared for the formation of voids. The simulations showed distinct differences in void fraction in the cross-section of the column. It is shown that throughout the range of considered water velocities, heterogeneous behaviour exists and cannot be neglected. The heterogeneity and onset of fluidisation behaviour obtained from the simulations and experimental observations were compared and found to agree reasonably well.